2003
DOI: 10.1161/01.str.0000098650.12386.b3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Etiologic Mechanisms of Strokes Secondary to Coronary Artery Bypass Graft Surgery

Abstract: Background and Purpose-Current research focused on stroke in the setting of coronary artery bypass graft (CABG) surgery has missed important opportunities for additional understanding by failing to consider the range of different stroke mechanisms. We developed and implemented a classification system to identify the distribution and timing of stroke subtypes. Methods-We conducted a regional study of 388 patients with the diagnosis of stroke after isolated CABG surgery in northern New England from 1992 to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
156
1
11

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(172 citation statements)
references
References 22 publications
4
156
1
11
Order By: Relevance
“…Our single-center, retrospective review of cardiac operations during a 10-year period found that stroke complications were infrequent. The overall stroke rate of 2.8% is similar to that reported in other studies [3][4][5][6][7][8][9][10]19].…”
Section: Commentsupporting
confidence: 88%
See 3 more Smart Citations
“…Our single-center, retrospective review of cardiac operations during a 10-year period found that stroke complications were infrequent. The overall stroke rate of 2.8% is similar to that reported in other studies [3][4][5][6][7][8][9][10]19].…”
Section: Commentsupporting
confidence: 88%
“…This differentiation was determined before the data were collected and was based on our specific institutional experience as well as previous reports that a significant proportion of postoperative strokes occur within the first 24 hours after CPB [10,19]. All stroke time data were reviewed by 3 investigators, and the temporal onset of the deficits was classified by consensus as either occurring within 24 hours from the onset of the procedure (≤24-hour group) or after 24 hours from the onset of the operation (>24-hour group).…”
Section: Classification Of Timing Of Strokementioning
confidence: 99%
See 2 more Smart Citations
“…47,59 Between 30-50% of perioperative strokes detected with brain imaging are due to cerebral macroembolism likely arising from the ascending aorta. 10,28,45,64,101 Encephalopathy and neurocognitive dysfunction are believed to result primarily from cerebral microembolism.. 3,18 ,20, 47,57,73,82,84,92 Microemboli are either gaseous or particulate in composition. Gaseous emboli can arise form an open left-sided cardiac chamber or from air entrained into the CPB circuit.…”
Section: Cerebral Embolismmentioning
confidence: 99%